The impact of vascular calcification among dialysis dependent South African CKD patients. A five year follow up study. Cardiovascular mortality and morbidity, ethnic variation and hemodynamic correlates - Simba, Kudakwashe (Department of Medicine, 2020)
BACKGROUND Vascular calcification is a major risk factor for cardiovascular morbidity and mortality in patients with end stage renal disease (ESRD). In Western countries, Blacks with ESRD appear to have lesser degrees of vascular calcification compared to non-Blacks. However, there is no published data on the association of ethnic differences in vascular calcification and survival in ESRD from Sub-Saharan Africa.